In situ Serial Trident Chop for Low-IOP Phacoemulsification without Nuclear Rotation: A Case Report - Lin HC; Lin YH (International Medical Case Reports Journal, 2025)
Hung-Chou Lin,1 Yung-Han Lin2 1Department of Ophthalmology, Dr. Lin’s Eye Clinic and Laser Vision Correction Center, Taoyuan City, Taiwan; 2Department of Medicine, Chung Shan Medical University, Taichung, TaiwanCorrespondence: Hung-Chou Lin, Department of Ophthalmology, Dr. Lin’s Eye Clinic and Laser Vision Correction Center, 437, Chingkuo Road, Taoyuan District, Taoyuan City, 330, Taiwan, Email joe8168@hotmail.comBackground: Phacoemulsification had been made efficient by hydrodissection, nucleus rotation, chopping, and using high vacuum to aspirate lens fragments under high hydrostatic pressure. Yet hydrodissection might be incomplete with the lens nucleus resisting rotation. Further vigorous hydrodissection might rupture the posterior capsule and forceful nuclear rotation might cause zonular dialysis. Encountered with such conditions, we present a case using an in situ serial trident chop technique and hydrodelineation independent of complete hydrodissection and nucleus rotation to avoid related complications.Case Presentation: A 61-year-old male patient with grade II nuclear opalescence received phacoemulsification from the author. Incomplete hydrodissection, inadvertent hydrodelineation and difficult nuclear rotation were noted during operation. The author turned to in situ serial trident chop without nuclear rotation under low intraocular pressure (IOP), which was done by dividing the nucleus into four fragments through three serial in situ horizontal chops in the 12 o’clock, 3 o’clock, and 10 o’clock directions, then the fragments were picked to the phaco tip by nucleus manipulator instead of high vacuum produced by phaco tip to reduce the hydrostatic pressure needed for keeping the safe depth of the anterior chamber. The resultant four small nuclear fragments were readily emulsified under a stable anterior chamber with an IOP of 20– 28 mmHg and cumulative dissipated energy of 3.28. The eye’s central corneal thickness increased from 522 μm before the operation to 540 μm on the following day.Conclusion: Phacoemulsification could be accomplished by in situ serial trident chop under low IOP and hydrodelineation without complete hydrodissection or nuclear rotation for grade II nuclear opalescence, although further investigation is needed to confirm its safety and efficacy.Keywords: chop in situ, low intraocular pressure, phacoemulsification, trident chop, without rotation